Histoplasma capsulatum Infection in an Allogeneic Hematopoietic Stem Cell Transplant Patient Receiving Voriconazole Prophylaxis - Vaibhav Agrawal; Bryan J. Brinda; Sherif S. Farag (Case Reports in Hematology)
Histoplasma capsulatum infection is a rare complication in the allogeneic stem cell transplant patients. Minimal guidance exists on how to appropriately manage histoplasmosis in these patients. We report a patient who developed Histoplasma pneumonia while receiving voriconazole prophylaxis at a therapeutic trough level. The patient experienced significant clinical improvement after initiation of itraconazole pharmacotherapy. We recommend a lower threshold for evaluation for histoplasmosis in allogeneic hematopoietic stem cell transplant recipients who live in endemic regions, regardless of their antifungal prophylactic regimen.